Determination of cadmium and copper in the blood of workers in goldsmithing workshops in Najaf Governorate: A field and analytical study - Zaid Mohamed Mohamed Ibrahim; Mohanad Halboos (Magazin of Al-Kufa University for Biology, 2023)
Najaf Governorate in Iraq is considered one of the areas witnessing intense activity in the goldsmithing industry. Pollution with heavy metals such as cadmium and copper is a serious health problem that affects human health and the environment. This research aims to estimate the levels of cadmium and copper contamination in the blood of workers in goldsmithing workshops in Najaf Governorate, especially workers exposed to pollution and smoking factors. The study was carried out by implementing a field and analytical study, which included a sample of 50 smokers in goldsmithing workshops. Blood samples were analyzed to determine the extent of the impact of workshop work on the levels of cadmium and copper contamination in the blood, and evaluated in comparison with previous related studies. The results showed that working in goldsmithing workshops exposes workers to high levels of cadmium and copper contamination, as the levels of cadmium in the blood were (0-1.7) parts per million compared to previous studies, which were (0-0.7) parts per million, and the levels of copper in the blood were (0-1.7) ppm (5-7) ppm compared to previous studies (0-2) ppm. The results indicate the need to take preventive measures and measures to reduce pollution, improve the work environment in goldsmithing workshops, and educate workers about the dangers of heavy metal pollution and its impact on their health. The study period was from October 2022 to April 2023.